Inflammatory Bowel Disease Incidence and Prevalence in Southern Alberta - Faith G Davis; Michael G Grace; Noel Hershfield (Canadian Journal of Gastroenterology)
Incidence and prevalence rates of inflammatory bowel disease were estimated for 1976-81 in southern Alberta. Cases were identified using hospital and physician records and membership lists of the Canadian Foundation for Ileitis and Colitis. A mail survey was conducted to obtain demographic data. Population data were obtained from Statistics Canada. The overall prevalence rate of IBO in men was 69.1 per 105 and 97.6 per 105 in women. Incidence rates of IBD were 6.0 per 105 per year in men and 9.2 per 105 per year in women. These six differences were due to Crohn's disease as female incidence rates were twice that of male rates 6.3 per 105 per year versus 3. L per LOS per year. A bimodal age distribution and female predominance in the younger age groups was apparent for Crohn's disease.